Effects of aerial hypoxia and temperature on pulmonary breathing pattern and gas exchange in the South American lungfish, Lepidosiren paradoxa - Silva, Glauber S. F. da [UNESP]; Ventura, Daniela A. D. N.; Zena, Lucas A. [UNESP]; Giusti, Humberto; Glass, Mogens L.; Klein, Wilfried (Elsevier B.V., 2017)
The South American lungfish Lepidosiren paradoxa is an obligatory air-breathing fish possessing well-developed bilateral lungs, and undergoing seasonal changes in its habitat, including temperature changes. In the present study we aimed to evaluate gas exchange and pulmonary breathing pattern in L paradoxa at different temperatures (25 and 30 degrees C) and different inspired O-2 levels (21,12,10, and 7%). Normoxic breathing pattern consisted of isolated ventilatory cycles composed of an expiration followed by 2.4 +/- 0.2 buccal inspirations. Both expiratory and inspiratory tidal volumes reached a maximum of about 35 ml kg(-1), indicating that L paradoxa is able to exchange nearly all of its lung air in a single ventilatory cycle. At both temperatures, hypoxia caused a significant increase in pulmonary ventilation ((V) over dot (E)), mainly due to an increase in respiratory frequency. Durations of the ventilatory cycle and expiratory and inspiratory tidal volumes were not significantly affected by hypoxia. Expiratory time (but not inspiratory) was significantly shorter at 30 degrees C and at all O-2 levels. While a small change in oxygen consumption ((V) over dot O-2) could be noticed, the carbon dioxide release ('CO2, P = 0.0003) and air convection requirement ((V) over dot (E)/(V) over dot O-2, P = 0.0001) were significantly affected by hypoxia (7% O-2) at both temperatures, when compared to normoxia, and pulmonary diffusion capacity increased about four-fold due to hypoxic exposure. These data highlight important features of the respiratory system of L. paradoxa, capable of matching O-2 demand and supply under different environmental change, as well as help to understand the evolution of air breathing in lungfish. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Dipnoi; Lung ventilation; Thermal variation; Buccal pump